ENDANG SRI MARUTI - admin, Keguru (Penerbit STKIP PGRI Bangkalan, 2019)
Abstract The purpose of this study was to determine the extent to which the performance of dolanan dance learning in grade 4 elementary school using SAVI approached teaching materials and to determine the response of students and teachers in dolanan song learning by using SAVI-related teaching materials for Grade 4 students. This research is a type of descriptive qualitative research using a phenomenological approach. Data collection techniques are based on data sources, namely RPP, syllabus, observation, interviews, closed questionnaires, and documentation. Data analysis techniques used are data analysis of Miles and Huberman models. Based on the results of the study it can be concluded that the learning of dolanan songs in grade 4 elementary school using SAVI teaching materials is relatively innovative. Based on the results of interviews, documentation, observation and giving questionnaires, students 'responses were categorized as good, students' enthusiasm in learning Javanese language lessons, especially the material of dolanan songs became increased. Students become fond of learning because in addition to singing there are also games in it, and student collaboration is also formed in group activities so as to foster a positive attitude towards students in their social interactions.